(untitled) (Per Musi, 2012)
Review of the book: The paths of the music. Europe and Argentina of Pablo BARDIN, Melanie PLESCH, Pola SUÁREZ URTUBEY, Federico MONJEAU, Pablo KOHAN, Pablo GIANERA. Jujuy : EdiUnju (University Press of Jujuy), 2008, 227 pp.